Utilizing AI to Optimize Product Sales at UD Bima Baru - Widayanti, Lilis; Vivi Aida Fitria; Adriani Kala’lembang; Widya Adhariyanty Rahayu; Suastika Yulia Riska (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The study aims to evaluate the effectiveness of activities in reaching participants, achieving training goals, improving proficiency, and enhancing sales through AI technologies. Method: This study teaches and evaluates the use of AI in sales optimization through lectures, demonstrations, tasks, and question-and-answer meetings. How well the activity worked is judged by how well the players met the goals and understood the material. Practical Application: The participants from UD. Bima Baru showed high levels of enthusiasm and engagement during each session of the activity. This indicates the possibility for enhancing their skills, operational efficiency, and revenue, while also fostering collaboration and fostering creativity in the future. Conclusion: Artificial intelligence (AI) has considerable potential to augment sales for MSMEs, like UD Bima Baru, through data-driven decision-making. Effective AI adoption requires practical experience, underscoring the significance of collaboration between academia and MSMEs in providing education, training, and mentorship. This collaboration fosters technological adoption and enhances local economic growth by generating practical, concrete ideas. Future training must include sequential courses for MSMEs to leverage AI.